SELLING-AND-BUYING TRANSACTION PATTERNS IN A TRADITIONAL MARKET: A GENERIC STRUCTURE POTENTIAL APPROACH - Fahmi Reza Alfani; Sukarno Sukarno; Akhmad Haryono (UIN Raden Mas Said Surakarta, 2021)
This research aimed to investigate the patterns of selLing-and-buying transactions in a traditional market. The data sources of this research were the the sellers and the buyersin beef, chicken, fruit, grocery, and vegetable shopsof Pasar Waru, a traditional market, in Sidoarjo, Indonesia. The data were in the form of transactional conversations between the sellers and the buyers. Qualitative method was applied in this research by using the formula of generic structure potential theory proposed by Halliday & Hasan (1985) to describe the patterns of buying-and-selling transaction in the market. The result shows that generic structure elements in some shops at Pasar Waru comprises: greeting (G), sale initiation (SI), sale enquiry (SE), sale request (SR), sale compliance (SC), sale (S), purchase (P), purchase closure (PC), and finish (F). The grocery, beef, and chicken shop had a similar structure of G^SR^SC^S^P^PC, whereas the fruit shop showed its actual structure G^SI^SE^SR^SC^S^P^PC. Meanwhile, the vegetable shop had G^SI^SR^SC^S^P^PC structure.Â As a whole, the five shops produced generic potential structure [(G).^] [ SR^ SC ^S^] P^PC.